Incomplete data from the Hiperdia program in Primary Healthcare Centre in Marabá, Pará (Research, Society and Development, 2021)
The Hiperdia program is fundamental for the screening, prevention, treatment of Arterial Hypertension and Diabetes Mellitus in Brazil. For that, a registration form with data from the patient assisted by the program is used, which will be sent to the Ministry of Health. However, it is clear that some forms do not contain data filled in their entirety within the Primary Healthcare Centre (PHC). Therefore, the objective of this study is to analyze the incompleteness of the Hiperdia files in PHCs in the city of Marabá-PA. This is a cross-sectional observational study, carried out in three PHCs in Marabá in 2020. 305 registration forms were analyzed, checking their incompleteness index with the help of an online questionnaire for data collection. Then, the EpiInfo program was used to measure the degree of confidence and the data were tabulated using the Microsoft Excel program. The incompleteness of the categories that make up the registration form received classification criteria that ranged from “excellent” to “very poor”, being considered excellent those categories that had the lowest incompleteness index. It was found that most of the categories were classified as “poor” or “very poor”. This result shows that the use of the Hiperdia program presents weaknesses in the city of Marabá. As a result of, the population of the city that depends on the program ends up not having ideal access to health, since the incomplete transfer of their data to the Ministry of Health makes it difficult to create health strategies and reduces the supply of drugs to patients in the municipality.